Morphometric, Nutritional, and Phytochemical Characterization of Eugenia (Syzygium paniculatum Gaertn): A Berry with Under-Discovered Potential - Jeanette Carrera-Cevallos; Christian Muso; Julio C. Chacón Torres; Diego Salazar; Lander Pérez; Andrea C. Landázuri; Marco León; María López; Oscar Jara; Manuel Coronel; David Carrera; Liliana Acurio (Foods)
Magenta Cherry or Eugenia (Syzygium paniculatum Gaertn) is an underutilized berry species with an interesting source of functional components. This study aimed to evaluate these berries’ morphometric, nutritional, and phytochemical characteristics at two ripening stages, CM: consumer maturity (CM) and OM: over-maturity. Morphometric analysis revealed size and weight parameters comparable to commercial berries such as blueberries. Fresh fruits were processed into pulverized material, and in this, a proximate analysis was evaluated, showing high moisture content (88.9%), dietary fiber (3.56%), and protein (0.63%), with negligible fat, indicating suitability for low-calorie diets. Phytochemical screening by HPLC identified gallic acid, chlorogenic acid, hydroxycinnamic acid, ferulic acid, quercetin, rutin, and condensed tannins. Ethanol extracts showed stronger bioactive profiles than aqueous extracts, with significant antioxidant capacity (up to 803.40 µmol Trolox/g via Ferric Reducing Antioxidant Power (FRAP assay). Fourier-transform infrared spectroscopy (FTIR) and Raman spectroscopic analyses established structural transformations of hydroxyl, carbonyl, and aromatic groups associated with ripening. These changes were supported by observed variations in anthocyanin and flavonoid contents, both higher at the CM stage. A notable pigment loss in OM fruits could be attributed to pH changes, oxidative degradation, enzymatic activity loss, and biotic stressors. Antioxidant assays (DPPH, ABTS, and FRAP) confirmed higher radical scavenging activity in CM-stage berries. Elemental analysis identified minerals such as potassium, calcium, magnesium, iron, and zinc, although in moderate concentrations. In summary, Syzygium paniculatum Gaertn fruit demonstrates considerable potential as a source of natural antioxidants and bioactive compounds. These findings advocate for greater exploration and sustainable use of this native berry species in functional food systems.